2012
DOI: 10.1117/12.999269
|View full text |Cite
|
Sign up to set email alerts
|

Research of dynamic detecting the raw silk fineness on line by a linear CCD and FPGA

Abstract: A new design scheme has been proposed that aim to realize real time, on line raw silk diameter measurement based on linear CCD (Charge Coupled Device) and FPGA (Field Programmable Gate Array).In this system, the samples of raw silk are placed in parallel light which reflect light through macro imaging is received by CCD image sensor. The research on how to improve precision of the system from theoretical approach to various functional modules parameter optimization. What's more, effects are solved in instabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Therefore, increasing numbers of methods are being studied for use in measuring yarn evenness. Some methods being developed may be more accurate, their operations may be easier, or their speeds may be faster [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, increasing numbers of methods are being studied for use in measuring yarn evenness. Some methods being developed may be more accurate, their operations may be easier, or their speeds may be faster [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The system consisted of a CCD camera which records the yarn shadow and a photo receiver which records the light diffused from the yarn. Using this system, the signal is used to express the change of the yarn diameter [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the development of optoelectronic technology, the range of the applications based on the CCD (Charge-coupled Device) sensors becomes wider and wider. Studies using this technique to detect the appearance of raw silk have been reported [1,2]. However, most of research are about processing the signal collected by CCD sensor rather then processing the image collected by CCD sensor.…”
Section: Introductionmentioning
confidence: 99%